The Strategic Role of Human Resources in Green Industry: Conceptual Integration between ESG Principles and Green HRM Practices - Podungge, Robiyati; Valentina Monoarfa (Samudra Publisher, 2025)
The accelerating transition toward sustainable industries demands strategic human resource management that integrates Environmental, Social, and Governance (ESG) principles with Green Human Resource Management (GHRM) practices. Despite global recognition, conceptual and operational integration between ESG and GHRM remains limited, particularly in Asia, where adoption rates and standardized performance indicators are still low. This study aims to identify and map international publication trends, thematic structures, and research gaps in ESG–GHRM integration, while proposing a conceptual framework to guide future research and practice. Employing a systematic literature review (SLR) guided by the PRISMA 2020 protocol and supported by bibliometric analysis using VOSviewer, the study synthesizes findings from 26 peer-reviewed articles published between 2020 and 2025, retrieved from Scopus, ScienceDirect, and Google Scholar. The bibliometric mapping reveals five dominant thematic clusters: green recruitment, green training, green performance appraisal, pro-environmental employee behavior, and ESG-linked sustainability performance. Emerging research directions include the role of green transformational leadership, digital transformation in sustainable HRM, and culturally grounded leadership models such as Mo’odelo Leadership. Findings indicate that strong GHRM adoption correlates positively with environmental commitment, organizational adaptability, and innovation in sustainability practices. However, research gaps remain in addressing the social and governance dimensions of ESG, developing standardized measurement frameworks, and expanding studies to underrepresented regions such as Southeast Asia. The study contributes to theory by providing evidence-based recommendations for aligning HR policies with sustainability goals. These insights hold significant implications for policymakers, industry leaders, and scholars in fostering resilient, ethically governed, and environmentally responsible organizations.